The place of financial and economic knowledge in structure of criminalistic science - Kovgan, Zhanna I. (Journal of the Belarusian State University. Law, 2019)
In article financial and economic knowledge are considered within criminalistics about which structure in scientific literature discussions are conducted. The analysis of opinions of scientists showed that financial and economic knowledge organically fits into classical four-unit system of criminalistics that expands and changes contents of its separate sections. By results of the conducted research the place of financial and economic knowledge in the called science is determined. By the author it is seen that the called knowledge can be applied to carrying out the analysis, synthesis and other methods. Within the criminalistic equipment, it is advisable, to apply financial and economic knowledge in case of a criminalistic research of documents and creation of criminalistic accounting. One more section of criminalistics which, in our opinion, can include the questions relating to financial and economic knowledge is criminalistic tactics, namely: tactics of carrying out separate legal proceedings; use of special knowledge in disclosure and investigation of crimes, appointment and production of examination. Financial and economic knowledge can be applied in case of investigation of a wide range of crimes therefore their place in private criminalistic techniques, investigations of separate crimes.
Keywords: financial and economic knowledge; criminalistic knowledge; criminalistics; criminalistics subject; criminalistic equipment; criminalistic tactics; criminalistic technique